PELAKSANAAN PROSEDUR MEMBERSIHKAN TOILET PUBLIK AREA PADA HARRIS HOTEL BATAM CENTER - Umam, Khotibul; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
HARRIS Hotel Batam Center is a 4 star hotel located right in Batam City Center which can be accessed just by walking to Mega Mall and International Ferry Terminal Batam Center, precisely located at Jl. Engku Putri, Tlk. Tering, District. Batam City, Batam City. This research aims to determine the procedure technique for cleaning the public toilet area at HARRIS Hotel Batam Center and to find out the obstacles in implementing the procedure technique for cleaning the public toilet area at HARRIS Hotel Batam Center. The data collection techniques used in this research were observation studies, interviews, documentation and literature studies. The results of this research are that providing bathrooms that are clean, healthy and free from disease and annoying insects is one of the main tasks of the housekeeping floor section, so that guests feel at home staying at the hotel. The implementation of procedures for cleaning and preparing bathrooms at Harris Hotel Batam is very good, this is proven by its implementation which is carried out consistently by area public officer, supervisors and housekeeping HOD. Keywords: Harris Hotel Batam, Procedures, Toilet